Prostate cancer diagnosis: Efficacy of a simple electromagnetic MRI-TRUS fusion method to target biopsies. Issue 86 (January 2017) - Jelidi, Amina; Ohana, Mickael; Labani, Aïssam; Alemann, Guillaume; Lang, Herve; Roy, Catherine
Highlights: A very simple electromagnetic device for fusion with MRI examination during TRUS guided biopsies increases the detection of clinically significant prostate cancer. This device has advantages: a short time for the fusion registration, no additional cumbersome material and no intense training to be fluent with. Low or intermediate suspicious area for prostate carcinoma on mpMRI can be due to benign histological abnormalities or high grade prostatic intraepithelial neoplasia. Abstract: Objective: To assess that transrectal ultrasound guidance (TRUS) targeted biopsies (TB) aimed with an easy to use electronic real-time fusion registration device have a higher rate of prostate cancer (PC) detection than standard biopsies (SB). Material and methods: This prospective study included 130 patients referred for TRUS biopsies after suspicious MRI. They underwent 16-core SB and 2 to 3 cores in each MRI suspicious area, using a fusion software. We noted SB and TB positivity for PC and Gleason score (GS). We used the McNemar test to compare SB and TB, with a statistical significance p < 0.05. Results: Among 130 patients, 68.5% had PC. Additional time due to the fusion registration was 3.3 min. One hundred fifteen patients (88.4%) had pathological findings on the histological analysis (prostate cancer n = 89, others n = 26). TB diagnosed PC in 75 patients with negative SB. Positivity rate for PC was significantly higher for TB than SB (p = 0.03). Among highly suspicious MRI lesions, detection rate of histological abnormalities using SB and TB was 96% with 79.7% of PC. Most PC that TB diagnosed alone were clinically significant (86.3%). Conclusion: TRUS biopsies performed with a simple MRI and US electronic fusion is an unrestrainedly method to increase PC diagnosis.